Performance Evaluation of Rice Variety MTU 1281 through on Farm Trial in West Godavari District of Andhra Pradesh, India - Podapati Vinayalakshmi; N. Mallikharjuna Rao; G. Naveen Kumar; T. Srinivasa Rao (Archives of Current Research International, 2024)
An on-farm trial was conducted by Krishi Vigyan Kendra, Undi in farmer’s fields of West Godavari district to evaluate the performance of rice variety MTU 1281 on yield and economics of Rice crop during the kharif season for two succeeding years 2022 and 2023. The results of the study revealed that MTU 1281 variety registered higher yield i.e., 7261, 7078 and 7170 kg/ha than MTU 7029 variety (6504, 6625 and 6565 kg/ha) during both the years of study and in pooled data as well. When compared to farmers’ practice (Rs. 58,145 and Rs. 71,603/ha and 1.78:1, 1.98:1 during 2022–23, 2023–24, respectively) net returns and the B:C ratio were higher with MTU 1281 rice variety (Rs. 75,198 and Rs. 83,273/ha and 2.03:1, 2.16:1).